Characterization of microbiota diversity of field‐collected Haemaphysalis longicornis (Acari: Ixodidae) with regard to sex and blood meals. (2nd November 2018) - Zhang, Ruiling; Huang, Zhendong; Yu, Guangfu; Zhang, Zhong
Abstract : Haemaphysalis longicornis is a prominent tick species in China, and the major vector of an emerging tick‐borne disease: severe fever with thrombocytopenia syndrome (SFTS). Microbiome diversity of ticks is influenced by several factors. In this study, we investigated microbiome diversity in field‐collected female and male H . longicornis ticks and compared the microbial composition of fed and unfed ticks and of those feeding on different hosts using barcode sequencing of V3–V4 region of 16S RNA gene. Regardless of sex, host, and feeding status; the highest abundance among all samples was found for the genus Coxiella . The relative numbers of Coxiella sequences decreased with the length of the blood feeding, whereas the numbers of Staphylococcus and Corynebacterium increased gradually. The dominance of Coxiella across all samples indicates that it is an obligate symbiont of H . longicornis . Overall, higher microbiome richness was detected in male ticks than in female ticks. Fed ticks showed a more diverse microbe composition than unfed ticks, and ticks fed on goats exhibited the highest diversity. These findings of this study can serve as a basis for future studies of microbiota biology and interactions between the microbes and pathogens of H . longicornis .